Phase Pure 2D Perovskite for High-Performance 2D-3D Heterostructured Perovskite Solar Cells - Li, Pengwei (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.